3D printing of bending-dominated soft lattices: numerical and experimental assessment. Issue 11 (29th July 2022) - Graziosi, Serena; Ballo, Federico Maria; Libonati, Flavia; Senna, Sofia
Abstract : Purpose: This study aims to investigate the behaviour of soft lattices, i.e. lattices capable of reaching large deformations, and the influence of the printing process on it. The authors focused on two cell topologies, the body-centred cubic (BCC) and the Kelvin, characterized by a bending-dominated behaviour relevant to the design of energy-absorbing applications. Design/methodology/approach: The authors analysed the experimental and numerical behaviour of multiple BCC and Kelvin structures. The authors designed homogenous and graded arrays of different dimensions. The authors compared their technical feasibility with two three-dimensional-printed technologies, such as the fused filament fabrication and the selective laser sintering, choosing thermoplastic polyurethane as the base material. Findings: The results demonstrate that multiple design aspects determine how the printing process influences the behaviour of soft lattices. Besides, a graded distribution of the material could contribute to fine-tuning this behaviour and mitigating the influence of the printing process. Practical implications: Despite being less explored than their rigid counterpart, soft lattices are now becoming of great interest, especially when lightweight, wearable and customizable solutions are needed. This study contributes to filling this gap. Originality/value: Only a few studies analyse design and printing issues of soft lattices due to the intrinsic complexity of printing flexible materials.